LncRNA KCNQ1OT1 as a miR-26a-5p sponge regulates ATG12-mediated cardiomyocyte autophagy and aggravates myocardial infarction. (1st September 2021) - Li, Jinbei; Tong, Yalin; Zhou, Yanjun; Han, Zhanying; Wang, Xule; Ding, Tongbin; Qu, Yongsheng; Zhang, Zhiliang; Chang, Chao; Zhang, Xiaoli; Qiu, Chunguang
Abstract: Background: As a dominant cardiovascular disease, myocardial infarction (MI) causes a considerable mortality globally. KCNQ1 overlapping transcript 1 (KCNQ1OT1) was reported to be overexpressed in MI patients. However, the detailed mechanisms remain unclear. Methods: We analyzed the expression of KCNQ1OT1 in the serum of MI patients, and built ischemia/reperfusion (I/R) mouse and H/R-induced cell model. TTC staining was used to evaluate infarct size in mice. TUNEL was employed to assess cell apoptosis. QRT-PCR was performed to detect the expression of KCNQ1OT1 and miR-26a-5p. The formation of autophagosomes in cells was detected by immunofluorescence. Caspase3 activity was detected by the Caspase-3 Assay Kit. Autophagy and apoptosis-related proteins were assessed by western blotting. Luciferase reporter assay was used to assess the binding relationship of KCNQ1OT1 and miR-26a-5p and miR-20a-5p/ATG12. Results: KCNQ1OT1 was up-regulated while miR-26a-5p was decreased in MI patients, I/R mouse and H/R-induced cell model. KCNQ1OT1 knockdown inhibited cell autophagy and protected cardiomyocytes from apoptosis by up-regulating miR-26a-5p. Either KCNQ1OT1 knockdown or miR-26a-5p mimics caused inhibition of autophagy related 12 homolog (ATG12), which was the direct target of miR-26a-5p. In vivo, KCNQ1OT1 promoted cardiomyocytes apoptosis via miR-26a-5p/ATG12 pathway. Conclusion: KCNQ1OT1/miR-26a-5p/ATG12 axis regulated cardiomyocyte autophagy and apoptosis, both in vivo and in vitro . These data supported that KCNQ1OT1 inhibition might be a promising therapeutic option for protection after MI. Highlights: Elevated KCNQ1OT1 and reduced miR-26a-5p were observed in serum of MI patients and I/R-induced mouse model. Knockdown of KCNQ1OT1 suppressed H/R-induced cell autophagy and apoptosis. KCNQ1OT1 acted as a sponge of miR-26a-5p, and ATG12 was a target gene of miR-26a-5p. KCNQ1OT1/miR-26a-5p/ATG12 axis regulated autophagy and apoptosis.